Responses of canine periodontal ligament cells to bubaline blood derived platelet rich fibrin in vitro - Banyatworakul, Poranee (Sci Rep, 2021)
Platelet-rich fibrin (PRF) promotes wound healing by providing the release of growth factors. Here, the influence of Thai and Murrah bubaline blood derived PRF on canine periodontal ligament cells (cPDLs) was investigated. PRF was prepared from Thai and Murrah buffaloes with single centrifugation. Results demonstrated that Thai bubaline blood derived PRF exhibited fiber-mesh like morphology and contained more platelet entrapment than Murrah bubaline blood derived PRF. Both bubaline PRFs were able to degrade in vitro under condition with trypsin. Thai but not Murrah bubaline blood derived PRF promoted cPDLs proliferation in serum free and 2% serum culture conditions. Correspondingly, the significant upregulation of KI67 mRNA expression was observed in those cells treated with Thai bubaline blood derived PRF. However, both Thai and Murrah bubaline blood derived PRF accelerated cell migration in an in vitro wound healing assay and facilitated cell spreading. Further, cPDLs cultured in osteogenic induction medium supplemented with Thai bubaline blood derived PRF exhibited the increased mineral deposition in vitro. Frozen Thai bubaline blood derived PRF also promoted cell proliferation, KI67 mRNA expression, cell migration, and cell spreading in cPDLs. Taken these evidence together, bubaline blood derived PRF could provide potential benefits for canine periodontal tissue healing.